Application of Mind Mapping Learning Methods to Improve Activities and Results of Student Learning in 2013 Integrated Thematic Curriculum Learning in Class IV SDN 11 Air Kalam - Nelli Herawani; Hadiyanto Hadiyanto; Yanti Fitria (International Journal of Educational Dynamics, 2019)
This study aims to describe the application of the Mind Mapping method to Increase student activity and student learning outcomes in 2013 curriculum integrated thematic learning in class IV SDN 11 Air Kalam. This research is a class action research, which is a study developed jointly for researchers and decision makers about variables that are manipulated and can be used to make improvements. Repairs are carried out with two cycles, namely cycle I and cycle II. Data from research results can be grouped into two, namely quantitative and qualitative data. Quantitative data, namely data in the form of numbers while qualitative data in the form of descriptive. As the subjects in this study were fourth grade students of SD Kalam 11 Air Kalam which amounted to 20. Based on the results of the study, the activities of students in the first cycle were 78.5% experiencing an increase in the second cycle of 86%. Thus, it has increased by 7.5%. While the student learning outcomes obtained in cycle 1 were 13 students who completed with a percentage of 65% and in cycle 2 as many as 16 students who completed a percentage of 80%. Thus, the activities and student learning outcomes with the application of mind mapping methods in class IV of SD Kalam 11 Air Kalam were stated to have increased.